2020
DOI: 10.1158/1078-0432.ccr-20-0073
|View full text |Cite
|
Sign up to set email alerts
|

Medium-throughput Drug Screening of Patient-derived Organoids from Colorectal Peritoneal Metastases to Direct Personalized Therapy

Abstract: Purpose: Patients with colorectal cancer with peritoneal metastases (CRPMs) have limited treatment options and the lowest colorectal cancer survival rates. We aimed to determine whether organoid testing could help guide precision treatment for patients with CRPMs, as the clinical utility of prospective, functional drug screening including nonstandard agents is unknown.Experimental Design: CRPM organoids (peritonoids) isolated from patients underwent parallel next-generation sequencing and medium-throughput dru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 39 publications
6
126
0
1
Order By: Relevance
“…One patient received vandetanib (pan-tyrosine-kinase inhibitor) which strongly reduced organoid viability, however no clinical response was observed. For another patient, gemcitabine showed an initial partial clinical response but after two additional months of treatment, disease progression was again observed ( 26 ). Peritoneal CRC-metastases organoids were also treated for efficacy towards mitomycin C and oxaliplatin (commonly used in HIPEC; intra-peritoneal chemotherapy treatment) and showed a general resistance, corresponding with the high recurrence rates observed in clinic ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…One patient received vandetanib (pan-tyrosine-kinase inhibitor) which strongly reduced organoid viability, however no clinical response was observed. For another patient, gemcitabine showed an initial partial clinical response but after two additional months of treatment, disease progression was again observed ( 26 ). Peritoneal CRC-metastases organoids were also treated for efficacy towards mitomycin C and oxaliplatin (commonly used in HIPEC; intra-peritoneal chemotherapy treatment) and showed a general resistance, corresponding with the high recurrence rates observed in clinic ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The AUC of a DRC, which combines the potency and efficacy of a drug, is a robust parameter when aiming to compare one agent across multiple tissue lines exposed to the same concentration range and may be more accurate than IC 50 (50% inhibitory concentration) 24,25 . Lastly, for combination treatment two approaches were used to define in vitro response: analysing each agent separately for a combined response classification 19,21,23,26,27 or analysing the response to combination treatment directly in vitro 17,20,21,[26][27][28][29][30][31][32] . The CinClare trial and de Witte et al report evidence of synergism for combination treatment 26,32 .…”
Section: Analytic Validity: Pdo-based Drug Screen Experimental Set-upmentioning
confidence: 99%
“…The studies were heterogeneous, varying in study design, patient population and treatments (Table 1). All studies were observational, with the exception of the APOLLO trial which was the first study to offer patients assay-guided treatment 28 . The results encompassed a variety of tumour types and stages of disease.…”
Section: Clinical Validity: Correlation Of Pdo Drug Screen Sensitivity With Clinical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Another study in pancreatic cancer supported this notion and showed that organoids, although primarily clonal, maintain distinct patient phenotypes and respond differently to drug combinations 9 . Patient-derived pancreatic cancer or colorectal cancer organoids are now being used to predict therapeutic responses, and facilitate precision medicine for patients 10, 11 . PDO or PDX-derived organoids (PDxO) have also been described for hepatocellular carcinoma 12 , hepatoblastoma 13 and glioblastoma 14 , as well as prostate 15, 16 ; bladder 17 ; ovarian 1819 ; breast 20 ; gastric 21 ; lung 22, 23 ; esophageal 24 ; kidney 25 ; and head and neck 26, 27 cancers.…”
Section: Introductionmentioning
confidence: 99%